Why is Loose Part an important learning medium for early childhood development? - Budiarti, Erna; Darmayanti, Rani (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2020)
Early infants are good at imitation and are passionate learners who learn via play. They are curious and actively seek new information. To develop its qualities, early infancy needs appropriate play. Educational play materials and instruments are used in play. Loose sections media games help kids grow. This study reviews the literature on loose-part learning materials and suggests actions to improve early childhood development. A descriptive qualitative systematic literature review (SLR) using Miles and Huberman's analysis of 2010–2020 papers was used. The articles examined Google Scholar search results for